Instructorns resource manual (IRM) to accompany Wortman/Loftus/Weaver Psychology, 5th edition - Wortman, Camille B.; Loftus, Elizabeth F. 1944-; Weaver, Charles (Boston McGraw-Hill, 1999)
An integrated supplement package designed to enhance instruction using the 5th Edition of Psychology by Camille Wortman, Elizabeth Loftus, and Charles Weaver. It is divided into two sections: Section I outlines some suggestions for developing, organizing, preparing, and presenting an introductory psychology course; Section II consists of 18 units that correspond to the 18 chapters found in the Wortman, Loftus, and Weaver text. Each unit contains material designed to facilitate classroom presentation of topics covered in the text.
On disc label: Presentation manager by McGraw-Hill College to accompany Psychology fifth edition by Camille Wortman/Elizabeth Loftus/Charles Weaver.
CD-ROM.
Keywords: Psychology; Psychology -- Computer-aided instruction